1997
DOI: 10.1093/infdis/175.1.146
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Germination of Aspergillus fumigatus Conidia on Cultured A549 Pneumocytes

Abstract: Invasive pulmonary aspergillosis is acquired through inhalation of conidia. Little is known about early interactions between Aspergillus fumigatus conidia and alveolar epithelial cells, so an in vitro model was developed to study binding between conidia and A549 cells, a line of type II pneumocytes. Conidia rapidly became attached to confluent monolayers of A549 cells in serum-free medium, reaching a plateau within 40 min. Scanning electron microscopy (EM) showed a random pattern of early adherence; viable con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 18 publications
2
61
0
Order By: Relevance
“…Previous research has highlighted that L-ficolin is able to function as an opsonin and enhance phagocytosis of S. Typhimurium and S. agalactiae (14,15). Due to the small size of the conidia, they can penetrate deep into the lungs, where they initially encounter the lung epithelium, in particular, type II pneumocytes (35). Ficolin-A mRNA has been observed to be most highly expressed in the liver and spleen; however, ficolin-A mRNA has also been observed to be expressed in the lung, suggesting the potential for its role in lung defense (36).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has highlighted that L-ficolin is able to function as an opsonin and enhance phagocytosis of S. Typhimurium and S. agalactiae (14,15). Due to the small size of the conidia, they can penetrate deep into the lungs, where they initially encounter the lung epithelium, in particular, type II pneumocytes (35). Ficolin-A mRNA has been observed to be most highly expressed in the liver and spleen; however, ficolin-A mRNA has also been observed to be expressed in the lung, suggesting the potential for its role in lung defense (36).…”
Section: Discussionmentioning
confidence: 99%
“…For monocytes and macrophages, a mannosyl-fucosyl receptor (39) and receptors inhibited by glucan and chitooligosaccharides (40) have been described. Conidial binding to pneumocytes was instead glycosphingolipid-mediated (41).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work by our laboratory and others has determined that A. fumigatus conidia are internalized by lung cells (DeHart et al, 1997;Paris et al, 1997;Wasylnka and Moore, 2002) endothelial cells (Paris et al, 1997;Wasylnka and Moore, 2002) and macrophages (Nessa et al, 1997;Wasylnka and Moore, 2002) in vitro. We have previously demonstrated that 100% of conidia internalized by A549 lung epithelial cells survive for at least 3 1/2 hours following uptake, whereas 70% of conidia internalized by J774 murine macrophages are killed within 6 hours.…”
Section: Introductionmentioning
confidence: 88%